1992
DOI: 10.3109/08990229209144776
|View full text |Cite
|
Sign up to set email alerts
|

A Psychophysical Comparison of Sensory and Affective Responses to Four Modalities of Experimental Pain

Abstract: It is generally accepted that the sensory and affective components of pain may be differentially associated with various acute and chronic diseases, and that some treatment regimens are best directed toward certain aspects of the pain experience. In addition, experimental animal models have been described that presume to assess either the sensory-discriminative aspects of phasic pain or the affective responses associated with tonic pain. The present psychophysical experiment directly compares the perceived int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
214
4
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(242 citation statements)
references
References 69 publications
20
214
4
4
Order By: Relevance
“…These erance and pain unpleasantness/intensity -even within the same-day measurement were virtually non-existent, which suggests that pain threshold and tolerance measure one aspect of pain (sensory-discriminative), while pain unpleasantness and intensity measure the other (affective-motivational). This is not in accordance with previous findings [25][26] suggesting high correlations between sensory and affective components of pain, especially in experimental settings.…”
Section: Resultscontrasting
confidence: 55%
“…These erance and pain unpleasantness/intensity -even within the same-day measurement were virtually non-existent, which suggests that pain threshold and tolerance measure one aspect of pain (sensory-discriminative), while pain unpleasantness and intensity measure the other (affective-motivational). This is not in accordance with previous findings [25][26] suggesting high correlations between sensory and affective components of pain, especially in experimental settings.…”
Section: Resultscontrasting
confidence: 55%
“…This in line with a relatively constant pain rating during prolonged cold pressor test (Rainville et al, 1992). Similarly, Bromm and Scharein (1982) showed that while pain ratings and evoked potentials did not show any change over time during several sessions of painful electrical stimulation, the GSR showed decreasing responses.…”
Section: Discussionmentioning
confidence: 49%
“…Since the stimulation period continued for 2 min in both the conditions that were scanned during the first as well as the second minute, it was not possible to assess the pain ratings for the first and second minute of scanning respectively without undue interference with the repeatability. However, the behavioural aspects including pain rating for the different time periods during prolonged cold pressor test stimulation has previously been thoroughly studied (Rainville et al, 1992;Tassorelli et al, 1995).…”
Section: Behavioural Resultsmentioning
confidence: 99%
See 2 more Smart Citations